Evaluating Computer Dependence in General Dentistry to Assess Mixed Reality Integration: A Retrospective Analysis - Husam Rassam; Laith Mahmood; Karam Rassam; Duc N. Lam (Saudi Journal of Medicine, 2026)
Mixed reality (MR), encompassing augmented reality (AR) and virtual reality (VR), is an emerging technology in dentistry that allows real-time integration of digital information into the clinician’s visual field. Contemporary dental workflows require frequent interaction with electronic health records, radiographs, and diagnostic tools, leading to workflow interruptions and increased cognitive load. This study aimed to quantify computer dependence across common dental procedures and identify those that may benefit most from MR integration. A retrospective observational study was conducted on 50 patients treated by a single general dentist. Patients were equally distributed among five procedure categories (n = 10 each): Extractions, Root Canal Treatments, Crowns, Fillings, and Prophylaxes. Computer dependence was quantified as active treatment time (seconds) divided by the number of clinician interactions with digital devices, expressed as seconds per interaction. A one-way ANOVA was used to evaluate differences among procedure types, and Welch’s t-tests compared Extractions with each of the remaining groups. Significant differences in computer dependence were observed among procedures. Extractions and Root Canal Treatments showed no statistically significant difference (p = 0.341), indicating similarly high reliance on digital interaction. In contrast, Crowns, Fillings, and Prophylaxes demonstrated significantly lower computer dependence than Extractions (all p < 0.001). Surgical and endodontic procedures exhibit the highest levels of computer dependence, suggesting they may benefit most from MR integration. Targeted implementation of MR could reduce screen shifts, decrease cognitive load, and improve procedural efficiency, supporting its prioritization in these workflows.